Immunohistochemical features of expression and distribution of antibodies to thyroglobulin in the thyroid glands of newborn rats after prenatal exposure of dexamethasone - Fedosieieva, O. V.; Pototska, O. I.; Федосєєва, Ольга Віталіївна; Потоцька, Олена Іванівна (Vinnytsya : National Pirogov Memorial Medical University, 2021)
In clinical practice, synthetic glucocorticoids, such as dexamethasone, are used to accelerate fetal maturation in pregnant women at risk of preterm birth. Increasing the concentration of cortisol in humans and other mammals often causes structural and functional changes in fetal tissues, preparing it for childbirth and extrauterine life, but they can have long-term consequences in the structural organization of organs postnatally. Despite the large number of studies on the effect of glucocorticoids on the fetus, there are almost no data on the prenatal effect of dexamethasone on the processes of synthesis and resorption of thyroglobulin by thyroid thyrocytes in the postnatal period of life. Therefore, the aim of the study was to determine the immunohistochemical features of expression and distribution of antibodies to thyroglobulin in the thyroid glands of newborn rats in normal and after prenatal exposure to dexamethasone. The study material was the thyroid gland of Wistar rats aged 1 to 7 days of postnatal development (54 animals): I group - intact animals (norm); ІІ group - control, animals which were injected with 0.9% NaCl solution at a dose of 0.05 ml to each fetus on the 18th day of dated pregnancy; III group - experimental animals, which were administered a solution of dexamethasone at a dilution of 1:40 at a dose of 0.05 ml to each fetus on the 18th day of the date of pregnancy operatively during laparotomy, by intrauterine, transdermal subcutaneous injection into the interscapular area (Ukrainian patent №112288). Thyroglobulin Antibody (2H11) monoclonal antibodies: sc-51708 from Santa Cruz Biotechnology, Inc. were used for immunohistochemical study. Photo documentation of the studied objects was performed using a "Primo Star" microscope (Carl Zeiss, Germany) using an AxioCam camera using the Zeiss Zen program (2011). Analysis of micropreparations of thyroid glands of intact and control rats showed invariance of thyroglobulin synthesis and its accumulation, which was expressed by sufficient immunohistochemical expression of antibodies to thyroglobulin (ТgAb+). Prenatal administration of dexamethasone leads to intensification of the processes of morphological development of hormone-producing structures (follicles and follicular epithelium), production, resorption and iodination of thyroglobulin. This is evidenced by immunohistochemical studies found in 1-3 days of the neonatal period. It should be noted that on the 7th day of life the newborn was found intense changes in the structure of the parenchyma of the thyroid gland of animals of the experimental group: increased relative percentage of follicle cavity due to increased number of large and medium, some follicles had no resorption vacuoles which was accompanied by a slowdown in the excretion of hormones into the bloodstream and led to overstretching of the follicles and, as a consequence, to the flattening of the thyroid epithelium. Intrauterine administration of dexamethasone leads to prenatal acceleration of structure formation, folliculogenesis and enhancement of hormone-producing function, which is confirmed by the peculiarities of immunohistochemical expression of TgAb. By the end of the neonatal period in rats prenatally exposed to dexamethasone, the thyroid gland is depleted of compensatory-reactive internal reserves, which is morphologically and immunohistochemically manifested by signs of hypofunction and hypertrophy. Thus, detected in the thyroid glands of animals prenatally exposed to dexamethasone, aberration of cytoplasmic expression of ТgAb+, intensification of colloidal expression of ТgAb+, flattening of thyroid epithelium, and the absence of resorption vacuoles are signs of impaired hormone-forming function, which is the morphological basis for the development of hypofunctional states and requires further study. У клінічній практиці синтетичні глюкокортикоїди, такі як дексаметазон, використовують для прискорення дозрівання плода у вагітних жінок з ризиком передчасних пологів. Підвищення концентрації кортизолу в організмі людини та інших видів ссавців нерідко викликає структурні та функціональні зміни в тканинах плода, готуючи його до пологів та позаутробного життя, але вони можуть мати віддалені наслідки в структурній організації органів постнатально. Попри велику кількість проведених досліджень щодо впливу глюкокортикоїдів на плід майже відсутні дані з пренатального впливу дексаметазону на процеси синтезу та резорбції тироглобуліну тироцитами щитоподібної залози у постнатальному періоді життя. Тому метою дослідження було визначення імуногістохімічних особливостей експресії та розподілу антитіл до тироглобуліну в щитоподібних залозах новонароджених щурів в нормі та після пренатального впливу дексаметазону. Матеріалом дослідження були щитоподібні залози щурів лінії Вістар у віці від 1 до 7 доби постнатального розвитку (54 тварини): І гр. - інтактні тварини (норма); ІІ гр. - контрольна, тваринам котрої вводили 0,9% розчин NaCl в дозі 0,05 мл кожному плоду на 18 добу датованої вагітності; ІІІ - експериментальні тварини, яким вводили розчин дексаметазону у розведенні 1:40 в дозі 0,05 мл кожному плоду на 18 добу датованої вагітності оперативно під час лапаротомії, шляхом крізьматкової, крізьоболонкової підшкірної ін'єкції у міжлопаткову ділянку (патент України №112288). Для імуногістохімічного дослідження використовували моноклональні антитіла Thyroglobulin Antibody (2H11): sc-51708 фірми Santa Cruz Biotechnology, Inc. Фотодокументацію досліджуваних об'єктів виконано з використанням мікроскопу "Primo Star" (Carl Zeiss, Німеччина) з використанням камери AxioCam за допомогою програми Zeiss Zen (2011). Аналіз мікропрепаратів щитоподібних залоз щурів інтактної та контрольної групи показав незмінність синтезу тироглобуліну та його акумуляції, що виражалось достатньою імуногістохімічною експресією антитіл до тироглобуліну (ТgAb+). Пренатальне введення дексаметазону призводить до інтенсифікації процесів морфологічного розвитку гормон-продукуючих структур (фолікулів та фолікулярного епітелію), продукції, резорбції та йодинізації тироглобуліну. Про це свідчать дані імуногістохімічного дослідження, виявлені у 1-3 добу періоду новонародженості. Слід відмітити, що на 7 добу життя новонародженого були виявлені інтенсивні перетворення у структурі паренхіми щитоподібної залози тварин експериментальної групи, а саме: збільшувався відносний відсоток площі порожнини фолікулів за рахунок збільшення кількості великих та середніх, у частини фолікулів не було резорбційних вакуолей, що супроводжувалося уповільненням виведення гормонів до кровотоку й призводило до перерозтягнення фолікулів і, як наслідок, до сплощення тиреоїдного епітелію. Внутрішньоплідне введення дексаметазону призводить до пренатального прискорення структуроутворення, фолікулогенезу та підсилення гормон-продукуючої функції, що підтверджується особливостями імуногістохімічної експресії ТgAb. До завершення періоду новонародженості у щурів, пренатально експонованих дексаметазоном, у щитоподібній залозі виснажуються компенсаторно-реактивні внутрішньоорганні резерви, що морфологічно та імуногістохімічно проявляється ознаками гіпофункції та гіпертрофії. Таким чином, виявлені у щитоподібних залозах тварин, пренатально експонованих дексаметазоном, аберантність цитоплазматичної експресії ТgAb+, інтенсифікація колоїдної експресії ТgAb+, сплощення тиреоїдного епітелію та відсутність вакуолей резорбції є ознаками порушення гормон-утворюючої функції тироцитів, що є морфологічним підгрунттям до розвитку гіпофункціональних станів, що потребує подальшого вивчення.
Імуногістохімічні особливості експресії та розподілу антитіл до тироглобуліну в щитоподібних залозах новонароджених щурів після пренатального впливу дексаметазону
Keywords: thyroid gland; immunohistochemistry; thyrocyte; thyroglobulin; dexamethasone; щитоподібна залоза; імуногістохімія; тироцит; тироглобулін; дексаметазон